Proceedings of the Third International Conference on Learning Analytics and Knowledge 2013
DOI: 10.1145/2460296.2460335
|View full text |Cite
|
Sign up to set email alerts
|

Assessing students' performance using the learning analytics enriched rubrics

Abstract: The assessment of students' performance in e-learning environments is a challenging and demanding task for the teachers. Focusing on this challenge, a new assessment tool, called Learning Analytics Enriched Rubric (LAe-R) is presented in this paper. LAe-R is based on the concept of assessment rubrics which is a very popular assessment technique in education. LAe-R contains "enriched" criteria and grading levels that are associated to data extracted from the analysis of learners' interaction and learning behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Modern scoring strategies can also involve multiple scorers, and in these cases it can be necessary to include procedures to resolve disputes (Johnson, Penny, & Gordon, 2000). Software can be used to make some or all of the judgements on a rubric (Dimopoulos, Petropoulou, & Retalis, 2013). The scoring strategy on the sample rubric is analytic and requires the user to consider some minimum requirements for particular levels.…”
Section: Scoring Strategy: Procedures Used To Arrive At Marks and Gradesmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern scoring strategies can also involve multiple scorers, and in these cases it can be necessary to include procedures to resolve disputes (Johnson, Penny, & Gordon, 2000). Software can be used to make some or all of the judgements on a rubric (Dimopoulos, Petropoulou, & Retalis, 2013). The scoring strategy on the sample rubric is analytic and requires the user to consider some minimum requirements for particular levels.…”
Section: Scoring Strategy: Procedures Used To Arrive At Marks and Gradesmentioning
confidence: 99%
“…These judgements are less complex and require less expertise; some analytic judgements on rubrics can even be made automatically by computers (Dimopoulos et al, 2013).…”
Section: Quality Definitions: Explanations Of Attributes Of Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we note limitations to the recent research literature that perhaps prompted the call for papers focused on assessment in PBL and PjBL. As we sought to include recently published studies, conducting a systematic literature search, we found that for K-12 settings, there was a significant focus on technology applications from design and implementation to scoring and analytics (Dimopoulos, Petropoulou, & Retalis, 2013;Redecker & Johannessen, 2013;Thomas, 2016). While these may be promising areas of research, we are skeptical that they afford the kinds of interactions we have detailed here.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…It is commonly known that instructors can customize adaptive rubrics according to the evolution of students' learning [Isbel and Goomas, 2014], [Rejab et al, 2011], and [Silva and Restivo, 2012]. Some systems can automatically score each criterion by collecting related data from the files of the CAA tools [Dimopoulos et al, 2013] and [Rayón et al, 2014], or from previous evaluations [Matthews et al, 2012] and [Cabrera and Villalon, 2013]. Other approaches allow users to customize the assessment process to a particular environment (allotted time, interacting device, etc.)…”
Section: Introductionmentioning
confidence: 99%